Penertiban Anak Jalanan oleh Satpol PP Di Limba B Kota Selatan Kota Gorontalo - Aldi Podungge; Funco Tanipu; Dewinta Rizky R. Hatu (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The phenomenon of street children in Gorontalo City represents a complex social problem influenced by economic factors, environmental conditions, and weak family supervision. The presence of street children not only affects their own lives but also raises public order issues. Efforts by the Public Order Agency (Satpol PP) to manage street children have been implemented, yet remain ineffective as children tend to return to the streets after being removed. This study aims to evaluate the implementation of street children management by Satpol PP in Limba B, South City, Gorontalo, and to identify the obstacles faced during its execution. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving both street children and Satpol PP officers. The data were analyzed descriptively to gain an in-depth understanding of the phenomenon. Findings indicate that street children primarily work as buskers, street performers, and beggars, with family economic conditions as the main factor. The management efforts are temporary and lack deterrent effects due to budget constraints, limited ongoing guidance, weak inter-agency coordination, and environmental and peer influences. A more comprehensive and sustainable strategy is needed through enhanced inter-agency cooperation, adequate guidance facilities, and a humanistic social approach to support children’s rights and effectively reduce the number of street children.